2007
DOI: 10.1111/j.1467-9507.2007.00382.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental Emotion Coaching and Dismissing in Family Interaction

Abstract: We observed the positive emotion socialization practice of parental emotion coaching (EC) and the negative socialization practice of emotion dismissing (ED) during a family interaction task and examined their effects on children's emotion regulation and behavior problems in middle childhood. Participants were 87 sociodemographically diverse families (children aged 8-11 years; 46 girls). Outcome measures included mother, father and teacher reports of emotion regulation and behavior problems. ED was a risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
236
3
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(257 citation statements)
references
References 49 publications
6
236
3
12
Order By: Relevance
“…On the other hand, parent behaviors that are inconsistent with emotion coaching have been shown to be associated with poorer functioning. Parents' minimization of their child's emotions predicts lower social competence, more avoidant coping, poorer emotion regulation, and greater behavior problems in middle childhood and early adolescence (Eisenberg et al, 1996;Lunkenheimer, Shields, & Cortina, 2007). Other research has shown that negative reactions to emotions and neglect of emotions predict low social and behavioral competence in a range of age-groups, from childhood through adolescence (Eisenberg, Cumberland, & Spinrad, 1998).…”
Section: Emotion Coachingmentioning
confidence: 99%
“…On the other hand, parent behaviors that are inconsistent with emotion coaching have been shown to be associated with poorer functioning. Parents' minimization of their child's emotions predicts lower social competence, more avoidant coping, poorer emotion regulation, and greater behavior problems in middle childhood and early adolescence (Eisenberg et al, 1996;Lunkenheimer, Shields, & Cortina, 2007). Other research has shown that negative reactions to emotions and neglect of emotions predict low social and behavioral competence in a range of age-groups, from childhood through adolescence (Eisenberg, Cumberland, & Spinrad, 1998).…”
Section: Emotion Coachingmentioning
confidence: 99%
“…Therefore, the findings from this study has significant implications for families as a whole, in terms of their roles and how they may influence children's brain anatomy as well as social and emotional development. As previous research has indicated, the types of meta-emotion approaches parents adopt may influence children's emotion regulation abilities and social competence skills (Lunkenheimer & Cortina, 2007;Wilson et al, 2012).…”
Section: Environmental Factors and Emotion Socializationmentioning
confidence: 99%
“…The types of meta-emotion approaches parents adopt are quite significant, as they have been found to be associated with children's socialization and emotion regulation abilities (Lunkenheimer & Cortina, 2007;Wilson et al, 2012). Children's abilities to regulate their emotions is associated with executive functions in their brains, which are also responsible for higher level thinking processes, such as attention, inhibitions of negative emotions, and memory (Graziano, Reavis, Keane, & Calkins, 2007).…”
Section: Significance Of Meta-emotion Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Exclusion criteria for the study included the following: children being outside of the age or grade range; mothers/female caregivers not residing with the child at least fifty percent of the time; and mothers/female caregivers being unable or unwilling to attend the laboratory session with their child. Father-child pairs were not eligible to participate, as some studies suggest mothers and fathers differ in their usage of direct ES (Eisenberg et al, 1996;Lunkenheimer, Shields, & Cortina, 2007;McElwain, Halberstadt, & Volling, 2007).…”
Section: Participantsmentioning
confidence: 99%